First stereo selective synthesis of 5-O-feruloyl-2-deoxy-d-ribono-γ-lactone. Issue 42 (19th October 2016) - Ganesh, K. Ravi; Rao, K. Raghavendra; Pratap, T.V.; Raghunadh, A.; Kumar, S. Praveen; Basaveswara Rao, M.V.; Murthy, C.; Meruva, Suresh Babu
Graphical abstract: Highlights: Established first total synthesis of 5- O -feruloyl-2-deoxy-d -ribono-γ-lactone. The synthesis began with economically benign protected ( R )-glyceraldehyde. The unreported O -PMB protected intermediates were synthesized. Employed Pinnick conditions for oxidation of terminal aldehyde. Optimized the O -PMB deprotection conditions and succeeded using CeCl3 ·7H2 O and NaI. Abstract: The first stereo selective synthesis of 5- O -feruloyl-2-deoxy-d -ribono-γ-lactone was achieved by coupling reaction of substituted ferulic acid and hydroxy methyl ribono lactone and followed by deprotection of O -PMB. The spectroscopic data were compared with the reported values and a clear indication to the absolute stereochemistry of the natural 5- O -feruloyl-2-deoxy-d -ribono-γ-lactone.